PENGARUH PROFITABILITAS, GROWTH OPPORTUNITY, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Rista Bintara (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
The purpose of this study are as follows: 1) To examine the effect of profitability on corporate value; 2) To examine the effect of growth opportunity on firm value; and 3) To examine the effect of capital structure on firm value; 4) To examine the extent to which Good Corporate Governance can moderate the relationship between profitability and firm value; 5) To examine the extent to which Good Corporate Governance can moderate the relationship between growth opportunity and firm value; and To examine the extent to which Good Corporate Governance can moderate the relationship between capital structure and firm value.The type of research used in this study is associative casual research (causal assosiative research). The population in this study are manufacturing companies listed in the Indonesia Stock Exchange Period 2012-2015. Sample selection by purposive sampling method. The method of analysis used to test the hypothesis is the Interaction Test.The results showed, 1) Profitability has a positive effect on Corporate Value; 2) Growth Opportunity has no effect on Corporate Value with negative direction; and 3) Capital Structure has a positive effect on Corporate Value; 4) The interaction between profitability and Good Corporate Governance has a significant and significant effect on Corporate Value with a positive relationship; 5) The interaction between Growth Opportunity and Good Corporate Governance is significant and significant to Corporate Value with negative relationship; and 6) The interaction between capital structure and Good Corporate Governance has significant and significant effect on Corporate Value with positive relationship.